2018
DOI: 10.1016/j.hrthm.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage angiography is associated with the incidence and number of magnetic resonance imaging–detected brain lesions after percutaneous catheter-based left atrial appendage closure

Abstract: MRI-detected ABLs are commonly observed after percutaneous LAAC. The number of LAA angiographies is significantly associated with the number of ABLs; however, the clinical implications of ABL have yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…It is also possible that the additional information gained by LAA angiography results in improved clinical outcomes such as need for device recapture and redeployment, completeness of seal, device embolization, perforation because of fewer deployments, strokes, and time with catheters in the left atrium and LAA. Weighing these potential benefits against the risks of LAA angiography will require future studies to address these questions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the additional information gained by LAA angiography results in improved clinical outcomes such as need for device recapture and redeployment, completeness of seal, device embolization, perforation because of fewer deployments, strokes, and time with catheters in the left atrium and LAA. Weighing these potential benefits against the risks of LAA angiography will require future studies to address these questions …”
Section: Discussionmentioning
confidence: 99%
“…Weighing these potential benefits against the risks of LAA angiography will require future studies to address these questions. 15…”
Section: Discussionmentioning
confidence: 99%
“…The PROTECT AF and PREVAIL trails have shown a significant reduction in bleeding events, but the same risk of stroke after percutaneous LAA occlusion as compared to warfarin [7,8]. Several studies have shown that acute brain lesions (ABL) can occur after LAAC [9][10][11]. The incidence has been described to be between 4.8% and 5.2% [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that acute brain lesions (ABL) can occur after LAAC [9][10][11]. The incidence has been described to be between 4.8% and 5.2% [9][10][11]. The clinical implications of ABLs is not fully understood, as the long-term clinical course of ABLs during followup has varied.…”
Section: Introductionmentioning
confidence: 99%
“…Bellman et al, in the issue of the Journal , have added to their prior short‐term study of silent brain lesions with a follow‐up MRI at 3 months in their cohort with abnormal postprocedural scans. In their original research, 12/25 (48%) had acute brain lesions with 3/12 (25%) of these being both DWI & FLAIR positive on MRI within 24 hr.…”
mentioning
confidence: 99%